Methodology of da'wah to the non-Muslim Chinese in the Malay archipelago: a preliminary observation - Chuah, Osman; Muhamad Shukri, Abdul Salam @ Zulkifli (Penerbit Universiti Malaya, 2006)
The Chinese is quite a big ethnic group in the Malay Archipelago (Nusantara) with their religious background different from the native people. They are however the targets of preaching by Muslims and Christians. Many writers had written about da'wah (Qaradawi 1988; Sidi Gazalba and Zainab Ismail 1983; Ghazali Darussalam 1996). Few researches, however, have been done on the rejection of Chinese towards Islam in Nusantara. This study indicates that most of the Chinese reject and oppose Islam. It is then a great challenge for preachers to present Islam to the non-Muslim Chinese here. The findings show that Islam must be presented in the comprehensive manner and a moderate way to not only clear the misconceptions of Islam but the right kind of faith and an attractive way of life. The preachers should also guide Muslim umma to respect the rights of non-muslim as enshrined in the Qur'an and the Sunnah.